Implementing Sustainable Development Goals (SDGs) at the Village Level: A Case Study of Ciambar Village, Sukabumi Regency, West Java, Indonesia - Nurhayati Nurhayati; Ravena Fatmawati; Ahla Ainus Salma; Neville Hendra Lee; Gracia Cinthya Martin; Diazahra Astono; Muhammad Roffi Abdullah Syafi’i; Valdis Ayomi (CV. AFDIFAL MAJU BERKAH, 2025)
The KUM-ITT program implemented in Ciambar Village, Sukabumi Regency, West Java, serves as a community-based approach to achieving the Sustainable Development Goals (SDGs) at the village level. The program focused on five key areas: strengthening local MSMEs, improving cooperative literacy, promoting environmental management through waste sorting and diaper recycling education, revitalizing village infrastructure, and empowering women’s and children’s health. Activities were carried out from July 2–11, 2024, engaging local residents, women’s groups (PKK), village officials, and university students. The results showed significant improvements in environmental awareness, infrastructure safety, nutritional knowledge, and economic capacity. The program also fostered active participation of vulnerable groups and strengthened cross-sector collaboration through the pentahelix model.